International talent flows in the light of educational systems of the world countries - Elina BENEA-POPUȘOI (Academy of Economic Studies of Moldova, 2021)
Today we work in the knowledge economy. Whoever owns the information, implicitly has economic power. In this research, we have looked at the migration of human capital and international talent flows through the prism of the educational systems of various countries. The object of our research is human capital, talents and their flows. As research methods we mainly used observation, comparison, analysis, synthesis and inductive reasoning. Inter alia, we have set out to tackle the causes of mass migration, including of the brain drain, and the consequences of these phenomena on the development of various states. We examined how the educational systems of the countries of the world influence the international talent flows, and what is the role of quality education. The paper can serve as an indicative map on the subject of international talent flows and will be particularly useful for researching both the international economic relations, and the global economic issues.